AUTHORIAL IDENTITIES IN CHEMISTRY AND LANGUAGE STUDIES: A CORPUS-BASED STUDY OF ENGLISH AND INDONESIAN RESEARCH ARTICLES - Roselani, Ni Gusti Ayu; Misma, Ro Daud (Linguistik Indonesia, 2024)
In academic writing, first-person pronouns not only replace the author’s name but also stand out as significant elements of traditional conventions. Consequently, an ongoing debate exists among scholars regarding the permissibility of specific first-person pronouns in certain disciplines. Despite extensive research both supporting and opposing the permissibility of specific first-person pronouns, more empirical evidence is needed, particularly in the fields of chemistry and language studies. This study examines the usage of first-person plural pronouns in English (we, our, and us) and Indonesian (kami, kita) and their clusivity in 40 research articles published by The Modern Language Journal, Nature Chemistry Journal, Litera Journal, and Alchemy Journal in the range 2021 to 2023. This research aims to highlight differences in how authors from diverse disciplines—chemistry and language studies—situate themselves in academic writing. To achieve this, we constructed two specialized corpora: the English Corpus of Language Studies and Chemistry (Encolanche) and the Indonesian Corpus of Language Studies and Chemistry (Indolanche). We utilized Sketch Engine, an online tool facilitating word listing and concordance, for inspection during the research process. A qualitative analysis explored clusivity and the author’s identity expressed through each linguistic form. Classification of authorial identities followed a taxonomy proposed by Martín (2003). Our results reveal frequent use of the pronoun we in Encolanche, with exclusive clusivity primarily employed to express the author as the experiment conductor. In contrast, Indolanche exhibits infrequent use of personal pronouns.